Business sustainability in Asia : compliance, performance and integrated reporting and assurance - Rezaee, Zabihollah, 1953-; Tsui, Judy S. L., 1955-; Cheng, Peter, 1948-; Zhou, Gaoguang, 1981- (Hoboken, New Jersey : John Wiley & Sons, 2019)
Get familiar with business sustainability in Asia Business Sustainability in Asia offers 12 chapters that cover different aspects of business sustainability with a keen focus on its implications in Asia. Anyone who is involved with business sustainability and corporate governance, the financial reporting process, investment decisions, legal and financial advising, assurance functions, and corporate governance education will be interested in this book. It examines business sustainability performance, reporting and assurance and their integration into strategy, governance, risk assessment, performance management, and the reporting process of disclosing governance, ethics, social, environmental, and economic sustainable performance. The book also highlights how people, businesses, and resources collaborate in a business sustainability and accountability model. - Develop an awareness and understanding of the main themes, perspectives, frameworks, and issues pertaining to corporate governance and business sustainability in Asia - Covers a variety of issues relevant to business sustainability in Asia - Authored by an expert who has written extensively on the subject - Understand why organizations worldwide recognize the importance of sustainability performance If you're a business leader, executive, auditor, or student looking to familiarize yourself with this emerging subject, Business Sustainability in Asia has you covered.
5 Institutional Settings in Asia Relevant for Business Sustainability6 Conclusions; 7 Chapter Takeaway; Endnotes; Chapter 4 Drivers and Sources of Business Sustainability Initiatives in the World Including Asia; 1 Executive Summary; 2 Introduction; 3 Global Mandatory Business Sustainability Initiatives; 4 Global Voluntary Business Sustainability Initiatives; 4.1 Global Reporting Initiative (GRI); 4.2 International Integrated Reporting Council (IIRC); 4.3 Sustainability Accounting Standards Board (SASB); 4.4 United Nations Global Compact
Includes index.
Print version record and CIP data provided by publisher; resource not viewed.
Includes bibliographical references and index.
Keywords: Social responsibility of business -- Asia; Corporations -- Asia -- Growth; Sustainable development -- Asia; Electronic books